Cervical necrotizing fasciitis: an uncommon sequela to dental infection - Moss RM. (2014)
Necrotizing fasciitis is a soft-tissue infection, usually polymicrobial, that causes necrosis of fascia and subcutaneous tissue while sparing skin and muscle. Although it more commonly involves the groin, abdomen, and extremities, it may also occur in the head and neck, usually secondary to dental infection. We report a case of cervical necrotizing fasciitis arising from a dental infection and review the cause, pathophysiology, diagnosis, and treatment of this potentially lethal entity. Early detection and interventions is emphasized. Extensive surgical debridement remains the mainstay of treatment. In addition, a clarification of the various eponyms it has gone under in the past is offered.